(untitled) (Revista Científica Integrada, 2023)
Objective: to report the experience of using the Singular Therapeutic Project as a teaching strategy on the health of the elderly. Methods: This is an experience report, carried out in a Basic Health Unit, with Family Health Teams, through six home visits by medical students, accompanied by the Community Health Agent, together with the teacher supervisor of the practical activity. In addition, six meetings were held to discuss the case and deepen the theory with the elaboration of a Unique Therapeutic Project, through the Case-Based Systematized Learning method, from September to December 2022, in a city on the coast of São Paulo, Brazil. Results: Risk assessment instruments were used to identify the problems in which the family was inserted. Theoretical-practical considerations emerged during the teaching-learning process of the case, with fortnightly deepening and improvement of skills on the health of the elderly, at each meeting. The management of the case, by means of a multidisciplinary team, allowed for greater scope and fulfillment of the demands. In the end, interventions were carried out, based on the needs presented.